Environmental research infrastructures are not (yet) ready to address ecosystem conservation challenge - Francisco J Bonet-García; Francisco Pando; María Suárez-Muñoz; Javier Cabello (Environmental Research Letters, 2023)
Research infrastructures (RIs) are tools intended to be a fundamental pillar in producing knowledge regarding the functioning of Earth’s vital systems. However, it is unclear to what extent these instruments can help to deal with global biodiversity challenges. This paper presents the first assessment of the alignment between the services provided by environmental RIs, and the knowledge requested to address three specific Global Challenges concerning biodiversity loss at a global level: threatened species, alien species and ecosystem conservation. We characterized the specific needs and Subchallenges behind each Global Challenge. We also collected the services provided by 44 relevant environmental RIs in a standardized form. Then, we assessed to what extent those services are useful to address the challenges’ needs. Our results show that RIs, as a whole, are better suited to respond to species-related challenges than to challenges involving whole ecosystems. Nevertheless, the overlap among challenges’ needs is quite significant. Nearly half of the identified needs are shared between the ‘threatened species’ and the ‘ecosystem conservation’ challenges. Most of the assessed RIs work with multiple Earth System’s compartments at the same time (e.g. terrestrial + marine, terrestrial + freshwater, etc). Regarding the spatial extent of the studied RIs, most of the ecosystem-based RIs focus on the country scale, while most of the RIs specialized in species-related challenges work at a global scale. Considering the needs required to address the studied challenges, we have found that the RIs assessed in this study do not cover several of them. These gaps comprise complex data combinations that the studied RIs do not provide. Most of these gaps can be attributed to the ‘ecosystem conservation’ challenge. We consider that RIs were generally built to support pure basic research, which hampers their contribution to combat biodiversity loss. Because of the urgency to address global biodiversity challenges, we suggest adding new functionalities to make RIs work as problem-oriented facilities.